Matching of Local Biomedical Ontology to Standard Biomedical Ontologies - Vataščinová, Jana; Zamazal, Ondřej; Vacura, Miroslav; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2018)
In many different areas, companies, projects, etc., there are many different ontologies that are being used even if they are describing the same or parts of the same domain. In order to benefit from larger public projects that are based on standard ontologies, ontology matching may be the answer for companies that are using their own local ontology.The goal of this thesis is to propose and realize a method of matching local biomedical ontology from MSD to standard biomedical ontologies that are being used in the PubChem project, in order to support data analysis in MSD. The first partial goal is to get acquainted with the theoretical background of the ontology matching. The second partial goal is to get acquainted with the PubChem repository for information on chemical substances. The third partial goal is to practically realize matching of MSD local biomedical ontology to standard biomedical ontologies.To achieve the goal, the matching tools LogMap, LogMapBio, AML, XMap, YAM-BIO, FCA-Map, PhenoMP, YAM++ and Silk were used, and the matching was carried out on the ontology level and on the instance level (Silk). On the ontology level, FCA-Map and PhenoMP did not return any results, and on the instance level, no results were achieved either.The results are achieved only from the matching on the ontology level. However, if the proposed method of matching of a local biomedical ontology to standard biomedical ontologies is to be followed in another matching process, the matching on the instance level can provide results in the different scenario.The contribution of the thesis is not only in the discovered alignments, but mainly in the proposed method for the matching process as the SALAR ontology might be replaced in the future and alignments for the new ontology will be needed. The thesis also shows how successful the ontology matching tools were in the given task. This can be an indicator for possible future matching processes.
Vedoucí práce: Ondřej Zamazal
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: kognitivní informatika [obor dipl. práce]; diplomové práce; master's theses